Your Child Has the Right to Grow: The Importance of Exclusive Breastfeeding to the Infants' Gross Motor - Elvira Ekklesia Aprilita; Rossyana Septyasih; Tutik Herawati (Budapest International Research and Critics University, 2022)
Breast milk is the best nutrient for infants because it contains ideal nutritional value for infants. Unmet nutritional needs of infants can pose a risk of chronic diseases, impaired cognitive development of children, and inhibition of the infant’s gross motor development. The study aims to prove how much influence exclusively breastfeeding affects the gross motor development of infants aged 7– 12 months. Methods: The research design used was a descriptive method, with a case study approach. The data source was selected by puposive sampling technique. Result: Result of research in the field at the last visit, it is found that 10-month-1-day-old infant who was given breast milk exclusively by her mother in gross motor development occurred according to her age, shown to be able to maintain the neck rigidly, sit alone for 60 seconds without being denied pillows, chairs or walls, and learned to stand with both feet refute some of her weight. While infant is 9-month-28-day-old who was not exclusively breastfed, gross motor development was not yet appropriate for his age, where the infant was only able to maintain his neck rigidly, but had not been able to sit alone for 60 seconds without being denied pillows, chairs or walls and learned to stand with both feet refuting some of his weight. Discussion: The result of the study can be used as motivation and a source of educational reference for breastfeeding mothers to provide breast milk exclusively to the infant because exclusive breast milk is proven to affect the gross motor development of the infant. Researchers are next expected to conduct a thorough study on factors that can affect the growth and development of the infant.